2020
DOI: 10.3390/app10124370
|View full text |Cite
|
Sign up to set email alerts
|

Listeners Sensitivity to Different Locations of Diffusive Surfaces in Performance Spaces: The Case of a Shoebox Concert Hall

Abstract: Diffusive surfaces are considered as one of the most challenging aspects to deal with in the acoustic design of concert halls. However, the acoustic effects that these surface locations have on the objective acoustic parameters and on sound perception have not yet been fully understood. Therefore, the effects of these surfaces on the acoustic design parameters have been investigated in a real shoebox concert hall with variable acoustics (Espace de Projection, IRCAM, Paris, France). Acoustic measurements have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Above all, the ISO 3382-1:2009 standard [26] deals with "performance spaces" but mostly refers to indoor environments (e.g., auditoria, concert halls, etc.). The topic of acoustical characterisation has already been examined in detail for indoor spaces through statistical analysis, in order to investigate the reproducibility of the measures, the accuracy of the parameter calculation [27], the influence of source-receiver position displacement, the measurement chains of different systems [28][29][30] and the sensitivity to materials characteristics variation [31][32][33]. The aim of this work was to compare two measurement techniques for ancient theatres, using the archaeological site of Tyndaris as case study [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the ISO 3382-1:2009 standard [26] deals with "performance spaces" but mostly refers to indoor environments (e.g., auditoria, concert halls, etc.). The topic of acoustical characterisation has already been examined in detail for indoor spaces through statistical analysis, in order to investigate the reproducibility of the measures, the accuracy of the parameter calculation [27], the influence of source-receiver position displacement, the measurement chains of different systems [28][29][30] and the sensitivity to materials characteristics variation [31][32][33]. The aim of this work was to compare two measurement techniques for ancient theatres, using the archaeological site of Tyndaris as case study [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of diffusive surfaces on the acoustic design parameters in a real shoebox concert hall with variable acoustics (Espace de Projection, IRCAM, Paris, France) were investigated by Shtrepi et al [16]. Acoustic measurements were performed in six hall configurations by varying the location of the diffusive surfaces over the front, mid and rear part of the lateral walls whilst the other surfaces were maintained absorptive or reflective.…”
Section: Listeners Sensitivity To Different Locations Of Diffusive Su...mentioning
confidence: 99%
“…Azad et al also investigated the combination of absorbers and diffusers, specifically how a diffuser directing the sound to an absorbent area in a non-diffuse room shows significant effects on the room acoustic parameters evaluated [ 29 ]. Shtrepi et al investigated how the location of diffusers and the distance from them can affect room acoustics, and showed that the perception of room acoustic parameters did not vary significantly with the location of the diffusers, nor were listeners sensitive to the location of the diffusers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%